The hidden price of Iceland’s green energy - Busch, Henner; Ramasar, Vasna; Carton, Wim; Guðmundsdottir, Hrönn (2018)
In times of runaway climate change, phasing out fossil fuels and increasing the share of renewables is imperative. But this transition is not without pitfalls as shown by a recent study of two large renewable projects in Iceland.